LOCAL AREA NETWORK LAN DESIGN FOR VIDEO CONFERENCE SERVICES AT SMK N 6 PALEMBANG - Maudy Risdiana; Meilyana Winda Perdana (International Journal Cister, 2022)
A computer network is a telecommunications network that allows computers to communicate with each other by exchanging data, the purpose of a computer network is to achieve its goals, every part of a computer network can request and provide services. The party that requests the service is called the client and the party that provides the service is called the server.network Service or network service is a service provided by a computer network that serves to provide convenience in using shared resources both software and hardware. To achieve the same goal, each part of the computer network will request and provide services (service). The party that provides the service is called the server and the one who requests the service is called the client. This architecture is referred to as client-server which is used in almost all computer network applications.